Effect of Akin Osteotomy on Hallux Valgus Correction After Scarf Osteotomy With Hallux Valgus Interphalangeus. (October 2019) - Kaufmann, Gerhard; Hofer, Philipp; Braito, Matthias; Bale, Reto; Putzer, David; Dammerer, Dietmar
Background: Recurrence after hallux valgus correction is a relatively frequent occurrence. Little is known about the importance of initial correction on radiologic outcome. The objective of our study was to determine postoperative radiologic parameters correlating with loss of correction after scarf osteotomy and the combined scarf/akin osteotomy, respectively. Methods: Loss of correction was evaluated based on a group of 53 feet with isolated scarf osteotomy (S group) and a group of 17 feet with combined scarf and akin osteotomy (SA group) in a retrospective analysis. The intermetatarsal angle (IMA), the hallux valgus angle (HVA), the distal metatarsal articular angle (DMAA), the proximal to distal phalangeal articular angle (PDPAA), the position of the sesamoids, and joint congruity were measured in weight-bearing radiographs preoperatively and postoperatively throughout a mean follow-up of 44.8 ± 23.6 months. Results: Loss of correction was comparable between the S and the SA group ( P > .05). In contrast, we found higher loss of HVA correction in the S subgroup with a preoperative PDPAA above 8 degrees ( P = .011), whereas loss of correction in the S subgroup below 8 degrees of PDPAA was comparable to the SA group. In the S group, loss of correction showed significant correlation with postoperative IMA ( P = .015) and PDPAA ( P = .008), whereas in the SA group a correlation could be detected for IMA only ( P = .045). Conclusion: In cases with a PDPAA above 8 degrees, we recommend a combined scarf/akin osteotomy to diminish the potential for loss of correction. Level of Evidence: Level III, therapeutic, retrospective comparative series.